2018
DOI: 10.1186/s13071-018-2663-5
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to deltamethrin by domestic and wild Triatoma infestans populations in the municipality of Toro Toro, Potosi, Bolivia

Abstract: BackgroundChemical control with pyrethroid insecticides has been effective in reducing endemic areas of distribution of Triatoma infestans in the Southern Cone, as well as Bolivia; this had considerably reduced the infestation of households in a large part of the territory. Nowadays, areas such as the Chaco and the Inter-Andean Valleys are regions where the reach of vector control strategies is becoming limited, and infestations of insecticide-treated households are reported more often. The objective of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
(32 reference statements)
0
6
0
1
Order By: Relevance
“…Ongoing transmission is primarily maintained by contamination with T. cruzi infected faeces of the predominant local triatomine insect vector, Triatoma infestans , which infests rural dwellings, especially in the Gran Chaco region, where vector control has had limited success [4]. Transmission can also be oral by consumption of triatomine faeces-contaminated food or congenitally, and via T. cruzi infected blood or organ donors.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing transmission is primarily maintained by contamination with T. cruzi infected faeces of the predominant local triatomine insect vector, Triatoma infestans , which infests rural dwellings, especially in the Gran Chaco region, where vector control has had limited success [4]. Transmission can also be oral by consumption of triatomine faeces-contaminated food or congenitally, and via T. cruzi infected blood or organ donors.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar do método de controle químico ser um dos mais utilizados, a sua manipulação exige cuidados para que danos ao meio ambiente e ao homem sejam minimizados. A resistência de algumas espécies de triatomíneos a inseticidas piretróides usados atualmente foram evidenciados em estudos o que pode dificultar a eficácia da sua utilização como método químico (ECHEVERRIA et al, 2018, REMO et al, 2020, PICCINALI et al, 2020.…”
Section: Método Químicounclassified
“…Some remnant triatomine populations present inside the houses after spray campaigns in endemic communities were found to be related to sylvatic colonies, suggesting that the sylvatic environment could be involved in the re-infestation process and may contribute to the re-establishment of populations in treated houses [ 29 ]. Furthermore, in the Chaco regions of Bolivia and Argentina, several studies have identified persistent triatomine bug populations inside houses, which were also resistant to pyrethroid and organophosphate insecticides [ 30 33 ].…”
Section: Introductionmentioning
confidence: 99%